2005
DOI: 10.1515/znc-2005-1-209
|View full text |Cite
|
Sign up to set email alerts
|

A New Flavonol Glycoside Derivative from Leaves of Moldenhawera nutans

Abstract: The ethyl acetate extract of leaves of Moldenhawera nutans Queiroz & Alkin (Leguminosae) furnished, besides methyl gallate and gallic acid, the flavonols named laricetrin, laricetrin 3-glucoside and laricetrin 3-galactoside as well as the new one named laricetrin 5-galloyl-3--d-xylopyranoside. It also was isolated from the hexane extract: -sitosterol, lupenone, -amyrinone, α-amyrinone, lupeol, -amyrin, α-amyrin and α-tocopherol. The antioxidant activities of flavonoids were measured through DPPH radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…An interesting case is that of a compound obtained from leaves of Moldenhawera nutans (Leguminosae) which was identified as 5-galloyllarycitrin 3-O-b-xylopyranoside. 269 However, in the 1 H NMR spectrum the chemical shift value for H-6 of the aglycone A-ring is essentially identical to that found in larycitrin itself, whereas H-2 of the sugar moiety shows a substantial downfield shift. This is a clear indication that the galloyl group should be placed at 2-OH of the sugar and not 5-OH of the aglycone.…”
Section: Flavonol O-glycosidesmentioning
confidence: 65%
See 1 more Smart Citation
“…An interesting case is that of a compound obtained from leaves of Moldenhawera nutans (Leguminosae) which was identified as 5-galloyllarycitrin 3-O-b-xylopyranoside. 269 However, in the 1 H NMR spectrum the chemical shift value for H-6 of the aglycone A-ring is essentially identical to that found in larycitrin itself, whereas H-2 of the sugar moiety shows a substantial downfield shift. This is a clear indication that the galloyl group should be placed at 2-OH of the sugar and not 5-OH of the aglycone.…”
Section: Flavonol O-glycosidesmentioning
confidence: 65%
“…A number of flavonol O-glycosides published as new in the 2004-2006 period have been omitted from Table 2 either because their characterisation appears incomplete, or difficulties exist in reconciling the structures proposed for them with the accompanying spectroscopic data. [251][252][253][254][255][256][257][258][259][260][261][262][263][264][265][266][267][268][269] In terms of incomplete characterisation, a common problem is that interglycosidic linkages and points of attachment between aglycone and glycosyl moieties are not always fully defined. This is particularly important where unusual linkages are suggested.…”
Section: Flavonol O-glycosidesmentioning
confidence: 99%
“…10 laricitrin is found in Moldenhawera nutans 11 and myricetrintrimethylether is a constituent of Bridelia ferruginea stem bark. 10 laricitrin is found in Moldenhawera nutans 11 and myricetrintrimethylether is a constituent of Bridelia ferruginea stem bark.…”
Section: And Wätjen Et Al 2 )mentioning
confidence: 99%
“…These three compounds were chosen since (i) it was hypothesized that the 2′,3′,4′-OH groups in ring B are primarily relevant for the life span extension induced by myricetin and (ii) due to the relevance of these compounds as ingredients of pharmacologically active herbs which are used in traditionally medicine: syringetin is a component of the leaves of Zanthoxylum bungeanum Maxim. 10 laricitrin is found in Moldenhawera nutans 11 and myricetrintrimethylether is a constituent of Bridelia ferruginea stem bark. 12 In addition to life span analyses, we also investigated the effect of the methylated derivatives on surrogate markers in the nematode, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, studies have shown a systemic anti-inflammatory action of the essential oil from leaves and resins of some Protium species (Siani et al, 1999;Rudiger et al, 2007). The main bio-active components in those resins, a-amyrin and b-amyrin (Figure 1), are pentacyclic triterpenes isolated from P. kleinii as well other plant species (Oliveira et al, 2005;Otuki et al, 2005b;do Vale et al, 2005). Some experimental evidence has pointed that a-amyrin exhibits systemic anti-nociceptive, antiinflammatory, antipruritic, hepatoprotective and gastroprotective properties, when assessed in vivo (Kweifio-Okai et al, 1994;Recio et al, 1995;Oliveira et al, 2004a,b).…”
Section: Introductionmentioning
confidence: 99%